Exosomes derived from 3D-cultured MSCs improve therapeutic effects in periodontitis and experimental colitis and restore the Th17 cell/Treg balance in inflamed periodontium - Yong Zhang; Jiayao Chen; Haijun Fu; Shuhong Kuang; Feng He; Min Zhang; Zongshan Shen; Wei Qin; Zhengmei Lin; Shuheng Huang (Nature Publishing Group, 2021)
Abstract Although mesenchymal stem cell-derived exosomes (MSC-exos) have been shown to have therapeutic effects in experimental periodontitis, their drawbacks, such as low yield and limited efficacy, have hampered their clinical application. These drawbacks can be largely reduced by replacing the traditional 2D culture system with a 3D system. However, the potential function of MSC-exos produced by 3D culture (3D-exos) in periodontitis remains elusive. This study showed that compared with MSC-exos generated via 2D culture (2D-exos), 3D-exos showed enhanced anti-inflammatory effects in a ligature-induced model of periodontitis by restoring the reactive T helper 17 (Th17) cell/Treg balance in inflamed periodontal tissues. Mechanistically, 3D-exos exhibited greater enrichment of miR-1246, which can suppress the expression of Nfat5, a key factor that mediates Th17 cell polarization in a sequence-dependent manner. Furthermore, we found that recovery of the Th17 cell/Treg balance in the inflamed periodontium by the local injection of 3D-exos attenuated experimental colitis. Our study not only showed that by restoring the Th17 cell/Treg balance through the miR-1246/Nfat5 axis, the 3D culture system improved the function of MSC-exos in the treatment of periodontitis, but also it provided a basis for treating inflammatory bowel disease (IBD) by restoring immune responses in the inflamed periodontium.